Numerical Investigation of Rainfall-Induced Landslide in Mudstone Using Coupled Finite and Discrete Element Analysis. (1st November 2018) - Hung, Ching; Liu, Chih-Hsuan; Chang, Chia-Ming
Abstract : In this study, the role of water infiltration on a rainfall-induced landslide in mudstone is investigated. Finite element analysis (FEA) and discrete element analysis (DEA) were employed to explore the driving mechanism in the prefailure regime and the dynamic runout process in the postfailure regime, respectively. The driving mechanism was revealed in terms of the pore water pressures, saturation, and displacement of the sliding zone. To account for water infiltration associated with the dynamic runout process of the landsliding, the sliding friction coefficient in DEA was examined. Based on the results, satisfactory agreement between the numerical analysis and landslide behavior was realized. In prefailure regime, the onset of landslide initiation was found through assessment of rapid change of source displacement (RCSD). The estimated seepage force was about 0.5 N at landslide initiation. In postfailure regime, the results demonstrate that water infiltration and transition in steepness play significant roles in the behavior of the dynamic runout process. The landsliding exhibited a maximum speed of 4.41 m/s and decelerated as it reached a more gentle slope. Overall, the study indicated that the coupling of FEA and DEA can be used to investigate the role of water infiltration and provide useful insights. The approach can be further applied for studies on many other rainfall-induced geohazards to disclose the role of water infiltration with the prefailure and postfailure characteristics.